Founder Competence, the Environment, and Venture Performance - Chandler, Gaylen N.; Hanks, Steven H. (Entrepreneurship Theory and Practice, 1994)
This research presents a parsimonious model of venture performance that incorporates individual founder, firm, and environmental characteristics. Specifically, It examines the moderating effect of founder competencies on venture performance in a sample of 155 manufacturing firms in northwestern Pennsylvania. In support of our hypotheses, the results indicate that individual level competencies moderate the relationships between the quality of the opportunity and firm performance and access to resource-based capabilities and firm performance.